PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN GAPOKTAN SINAR TANI DI DESA RULUNG RAYA KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Syarif Hidayatulloh; Sumaryo Gitosaputro; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The objectives of the research were to analyze the roles of agricultural extension workers to develop farmer groups in Rulung Raya village, Natar sub district, South Lampung Regency.  The research was conducted in December 2018 until February 2019.  The research method used is a survey method.  The respondents were 50 farmers randomly chosen from 615 farmers the members of Sinar Tani farmer group in Rulung Raya Vilaage. Data were analyzed using Rank Spearman correlation test.  The results showed that the roles of agricultural extension agents in terms of companion role, technical role, and communicator role have significant relationship with the development of farmer groups.  The role as organisator does not have relationship with the development of farmer groups. It is recommended for the agricultural extension workers to increase his roles in helping farmer groups development and for farmer groups to continue developing their group to reach their goals. Key words: agricultural extension workers, farmer groups.